THE STUDENTS’ PERCEPTION OF USING JEOPARDY IN TEACHING VOCABULARY - Andi Asmawati (ETERNAL (English, Teaching, Learning and Research Journal), 2022)
This study aimed to describe the students’ perception of using Jeopardy strategy in teaching vocabulary. This research used quantitative method. The respondents were 348 students of PIBA Program who were willing to fill out the distributed questionnaire through G-form. The instrument was closed-end and opened-end questionnaires. The data were analyzed quantitatively by interpreting percentages. The results indicated that the students perceive Jeopardy Strategy as an effective way to improve their English vocabulary. Most of the students Strongly Agreed that this strategy was interesting. However, the students sometimes prioritized gaining high scores over understanding the meaning and definition of the new words. Therefore, it is recommended to use Jeopardy strategy in teaching vocabulary by focusing students’ attention on the new words.